Thymosin beta 4 expression in normal skin, colon mucosa and in tumor infiltrating mast cells - Nemolato, S. (PAGEPress Publications, 2010)
Mast cells (MCs) are metachromatic cells that originate from multipotential hemopoietic stem cells in the bone marrow. Two distinct populations of MCs have been characterized: mucosal MCs are tryptase-positive while mast cells in skin contain tryptase and chymase. We now show that a sub-population of MCs is highly immunoreactive for thymosin β(4), as revealed by immunohistochemical analyses of normal skin, normal colon mucosa and salivary gland tumors. Four consecutive serial sections from each case were immunostained for thymosin β(4) (Tβ(4)), chymase, tryptase and stained for toluidine blue. In skin biopsies, MCs showed a comparable immunoreactivity for Tβ(4), chymase and tryptase. In normal colon mucosa the vast majority of mucosal MCs expressed a strong cytoplasmic immunoreactivity for tryptase and for Tβ(4), in the absence of chymase reactivity. A robust expression of Tβ(4) was detected in tumor-infiltrating and peritumoral mast cells in salivary gland tumors and breast ductal infiltrating carcinomas. Tumorinfiltrating MCs also showed a strong immunoreactivity for chymase and tryptase. In this paper, we first demonstrate that normal dermal and mucosal mast cells exhibit strong expression of thymosin β(4), which could be considered a new marker for the identification of mast cells in skin biopsies as well as in human tumors. The possible relationship between the degree of Tβ(4) expression in tumor-infiltrating mast cells and tumor behaviour warrants further consideration in future investigations.